Synthesis of liquid crystalline thioether-functionalized hydroxypropyl cellulose esters1. Issue 14 (14th April 2015) - Ohlendorf, Peter; Greiner, Andreas
<x xml:space="preserve">Abstract</x> Synthesis of novel, thermotropic hydroxypropyl cellulose (HPC) derivatives, completely esterified with functional thioether end groups and without crosslinking or chain degradation, showing cholesteric pitch heights in the visible range.